Cux2 serves as a novel lineage marker of granule cell layer neurons from the rhombic lip in mouse and chick embryos. Issue 8 (13th June 2016) - Capaldo, Emily; Iulianella, Angelo
Abstract : Background : The rhombic lip (RL), a germinal zone in the developing hindbrain, gives rise to all of the excitatory neurons of the cerebellum. It is presently unclear what factors distinguish between RL progenitor pools and play a role in differentiating the multiple cell types that arise from this region. The transcription factor Cux2 has been shown to play important roles in proliferation and differentiation of distinct neuronal populations during embryogenesis, but its role in cerebellar fate restriction is unknown.Results : Through expression analysis and genetic fate mapping studies we show that Cux2 is expressed in the RL of the fetal brain and is restricted to a pool of cerebellar granule cell precursors and unipolar brush cells. This restriction was remarkably specific because regardless of the timing of Cux2 reporter gene activation in the RL, only granule cell layer derivatives were labeled. However, the overexpression of Cux2 in naïve hindbrain tissue was insufficient to force progenitor cells to adopt a granule cell fate.Conclusions : Our results suggest that Cux2 delineates the pool of cerebellar granule cell layer progenitors from other RL and ventricular zone derivatives, and plays a role in fate restricting, but not differentiating, this population. Developmental Dynamics 245:881–896, 2016 . © 2016 Wiley Periodicals, Inc. Key findings: Cux2 is a novel and specific marker for granule cell neurons in the developing cerebellum. Cux2 activity in the rhombic lip fate maps to granule cells and unipolar brush cells. Granule cells are molecularly heterogeneous. Cux2 expression during cerebellar development is conserved in amniotes.